Relationship Between Money Supply and Economic Growth of Nepal: VECM Approach - Sigdel, Sahadev (Journal of Kathmandu BernHardt College, 2024)
Several theories elucidate the correlation between money supply and gross domestic product (GDP). Money supply refers to the total amount of money in circulation within an economy, encompassing currency, printed notes, funds in deposit accounts, and other liquid assets. Assessing the valuation of money supply assists analysts and policymakers in formulating or adjusting monetary policies, whether to increase or decrease the money supply. This valuation is crucial as it directly influences the business cycle, thus impacting the overall economy. This study delves into the relationship between money supply and economic growth in Nepal from 1975 to 2021 using co-integration, VECM, and causality tests. ADF tests reveal non-stationarity at the level but stationarity at the first difference, affirming long-run equilibrium with a single error correction term. VECM analysis unveils a notable ECT coefficient (-1.095592, p-value: 0.0042), indicating adjustments from past year deviations at a rate of 0.42%. Short-term dynamics demonstrate varying significance levels, with money supply (M2) leading to GDP, GDP leading to private investment (PI), private consumption (PC) leading to GDP, money supply (M2) leading to private investment (PI), money supply (M2) leading to private consumption (PC), and private investment (PI) leading to private consumption (PC), all showing significant unidirectional causal relationships at the 5% level. The study proposes increasing the money supply as a means to attain higher and swifter economic growth in Nepal.